Partial characterization of the mechanism(s) whereby apolipoprotein A-1 inhibits cholesterol crystal nucleation in the supersaturated model bile systems - SASAKI, Masatoshi; YAMAMOTO, Masao; AIHARA, Naoki; TAO, Seishi; YAMASHITA, Gunji; SAGAWA, Hiroshi; HATSUSHIKA, Sumie; TAZUMA, Susumu; MIZUNO, Shigeki; SASAKI, Harutoshi; KAJIYAMA, Goro (Kanzo, 1991)
An ultrastructural study was performed using supersaturated model bile systems to partially explore the mechanisms whereby apolipoprotein (apo) A-1 inhibits cholesterol crystal nucleation. Various lipid particles; vesicle, micelle, and non-micellar, non-vesicular discoidal particle, in model bile systems in the absence or presence of apo A-1 were consistently separated by gel permeation chromatography. Apo A-1 coeluted with discoidal particles. Discoidal particles without apo A-1 showed rapid transformation, i.e., multilamellar formation, followed by microcrystal nucleation, whereas those with apo A-1 showed very little transformation. In conclusion, apo A-1 stabilizes discoidal particles, consequently inhibiting cholesterol crystal nucleation.